Pembelajaran Berbasis Merdeka Belajar Kampus Merdeka (MBKM) dan OBE (Outcome-Based Education) di Perguruan Tinggi - Samsul Hadi; Deddy Ramadhani (Mataram University, 2026)
This study discusses learning based on Merdeka Belajar Kampus Merdeka (MBKM) and Outcome Based Education (OBE ) in higher education as a strategy for transforming higher education in Indonesia. MBKM is a policy that provides flexibility for students to gain learning experiences outside their study programs through various activities, such as internships, research, student exchanges, humanitarian projects, and entrepreneurship programs. Meanwhile, OBE is an educational approach oriented toward learning outcomes, where the entire learning process is designed to produce graduates who are competent, adaptive, and relevant to the needs of the workforce. This study aims to describe the concepts of MBKM and OBE , their implementation in higher education, as well as the advantages and challenges of their application. This study employs a systematic literature review method by analyzing 25 scientific sources published between 2019 and 2025, comprising accredited national journals indexed in Sinta 2–4, international journals indexed in Scopus and Google Scholar, as well as policy documents and official reports from the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. The literature was selected based on relevance criteria related to MBKM implementation, OBE frameworks, curriculum transformation, and graduate competency outcomes in higher education contexts. The results show that the integration of MBKM and OBE is able to create a more flexible, innovative, and student-centered learning system. In addition to improving academic competence, the implementation of these two approaches also develops students' soft skills, such as communication, collaboration, creativity, and critical thinking skills. However, their implementation still faces several challenges, including the readiness of human resources, curriculum adjustment, outcome-based evaluation systems, and limited industrial partnerships. Therefore, strengthening the curriculum, improving lecturers' competencies, and developing partnerships with various stakeholders are necessary to optimize the implementation of MBKM and OBE .